2020
DOI: 10.1186/s12939-020-01247-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial resources developed and trialled for Indigenous people with autism spectrum disorder and their caregivers: a systematic review and catalogue

Abstract: Background: People with autism spectrum disorder (ASD) face many psychosocial challenges throughout life, highlighting the need for programs and resources promoting psychosocial wellbeing. Indigenous peoples with ASD and/or other neurodevelopmental disorders must overcome cultural and social barriers to access such supports. This study aimed to identify psychosocial programs and resources developed worldwide for this population by systematically reviewing research evaluating programs aiming to promote the psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…A previous study by Shochet et al [ 16 ] had shown that Indigenous with ASD people living in remote areas had limited access to healthcare services. This is due to cultural and linguistic differences that are potential barriers to the diagnosis and treatment of this condition among the Amerindian population.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Shochet et al [ 16 ] had shown that Indigenous with ASD people living in remote areas had limited access to healthcare services. This is due to cultural and linguistic differences that are potential barriers to the diagnosis and treatment of this condition among the Amerindian population.…”
Section: Discussionmentioning
confidence: 99%
“…Further, what is considered atypical behaviour in Culturally and Linguistically Diverse (CALD) families may differ from families with European ancestry, delaying the recognition of autism traits [21][22][23]. For example, behaviours such as limited eye contact is considered typical behaviour in certain Indigenous Australian and Asian cultures [24,25] and may therefore go unrecognized as a potential indicator of autism. Subsequently, screening policies and early intervention services are largely not tailored towards the needs of CALD families, with various cultural and linguistic needs, many of whom experience challenges in accessing these services [26,27].…”
Section: Introductionmentioning
confidence: 99%